Uma proposição de ensino para o Ultimate Frisbee: do jogo às categorias pedagógicas freirianas - Silva, Angélica de Souza (2021)
The study in question intends to raise possible interrelations between the teaching of Ultimate Frisbee and the perspective of emancipatory education, according to Freire's epistemology. Observing the idiosyncrasies that make up Ultimate Frisbee, namely: self-arbitration; the mixed game/sport; and the “Spirit of the game”, conjecturing auspicious possibilities for problematizations relevant to the school field. It is, therefore, a question of analyzing whether, when thematizing the aforementioned knowledge of a sporting nature - understood as a manifestation of game, in effect, an expression of the body culture of movement - within the Physical Education curricular component, one will find " fecund soil” for the development of pedagogical categories (dialogicity, awareness, emancipation, praxis and autonomy) present in the sociocultural interactionist teaching approach, of which Paulo Freire is the main exponent. The main objective is to compare the above-mentioned modality, due to its structural particularities, in order to approach or impel the pedagogical categories present in Freire's thought, when being thematized in high school classes, due to the constitution of youth and their dilemmas constitutive and formative, although the referred teaching stage is not restricted. Therefore, a systematic literature review was undertaken in order to map Brazilian productions on the modality, in order to (scientifically) nurture a pedagogical proposition for teaching Ultimate Frisbee. When carrying out a systematic review of the national scientific production on the subject, an inopia of productions was identified, which indicated the relevance of this investigative action. So, after scrutinizing the idiosyncrasies of the game/sport, added to the results of the researched scientific literature and the foundations of Freire's thought and its pedagogical categories, the construction of a pedagogical proposition for the teaching of Ultimate Frisbee was fostered, which was divided into four moments, namely: the Initial Moment, of welcoming and surveying the universe of experiences of the students about the body culture of movement; the Investigative Moment, mapping the choice of the most significant issues that emerged from the dialogue with students; the Propositive Moment, in which existential situations and deepening of the problematizations are developed; and the Closing Moment, whose purpose is to close the cycle of pedagogical activities. Throughout the proposal, it is expected (very) to provide multiple openings and possibilities with which the Ultimate Frisbee teaching-learning process can give rise to and support the development of the pedagogical categories postulated by Freire (1980; 1989; 1992; 2018; 2019a). ; 2019b; 2019c; 2020). The aim is, in practice, to subsidize epistemologically the exercise of planning, intervention and evaluation of teachers in professional practice, consequently improving the organization and effectiveness of the pedagogical work, in particular with regard to the teaching of the aforementioned game/sport, under a perspective of emancipatory formation.